A Peek into Their Mind? An Exploration of Links Between Offense-Supportive Statements and Behaviors among Men Who Sexually Exploit Children and Adolescents Online - Paquette, Sarah (International journal of offender therapy and comparative criminology, 2023)
While forensic psychologists have some access to their patients’ thoughts when deciding on a diagnosis or appraising risk, others, such as police investigators, must rely on physical evidence and behavioral markers to make sense of a crime. Studies showing that offense-supportive cognitions constitute a risk factor for sexual offending, including offenses that take place on the internet, highlight the need for some access to offenders’ thoughts. This exploratory study examines the associations between offense-supportive statements about the sexual exploitation of children and adolescents and proxy behaviors. As part of PRESEL, a collaborative research project between Québec provincial police and academic researchers, the case files of 137 men convicted of using child sexual exploitation material or committing child-luring offenses were analyzed. Results showed that many meaningful risk factors and sexual offending behavioral markers were associated with the cognitive themes Sexualization of children, Child as partner, Dangerous world, Entitlement, and Uncontrollability. The use of encryption was negatively associated with the cognition Virtual is not real while Internet is uncontrollable was associated with fewer contacts with minors over the internet. Findings are useful for understanding the psychological needs that should be targeted in treatment, as well as helping prioritize police workloads.